Nová evidence-based kritéria pro posouzení vhodnosti lékového rezimu u seniorů. Kritéria STOPP (Screening Tool of Older Person's Prescriptions) a START (Screening Tool to Alert doctors to Right Treatment) - Topinková, E; Mádlová, P; Fialová, D; Klán, J (Vnitrni lekarstvi, 2008)
Drug prescribing in the old age is burdened by a significant number of prescribing errors often resulting in high rate of adverse drug events associated with increased morbidity, health care utilization and health costs. The revised 2003 Beers' Criteria represent the most widely used method for identification of high risk ("potentially inappropriate") medication in elderly persons. A standardized method for evaluating omission of potentially beneficial drugs has been lacking. The Beers' Criteria consist of the list of selected drugs with high potential of adverse drug events in old age and clinical conditions with relative contraindications of selected drugs (drug-disease interactions). Prescribing of these drugs should be avoided in older patients. However, several limitations prevent wider use of Beers' Criteria: several outdated drugs or drugs unavailable in Europe are listed, some controversial drugs with specific indications are on the list, drug-drug interaction and drug class duplications are not mentioned, and last but not least low user friendliness was criticized. To overcome these limitations, new STOPP and START Criteria were developed in 2007 to serve as a screening tool for comprehensive assessment of safety and quality of prescription in patients 65 years and older. In the current review article Czech version of both criteria are presented for the first time in the Czech literature. Using STOPP Criteria potentially inappropriate drugs are identified in drug regimen which could be stopped altogether or replaced by a safer drug alternative. Concomitant use of START Criteria will help the prescribing physician to consider the benefit of starting new drugs in selected clinical situations. Both screening tools represent a new method for improving quality of geriatric prescribing in clinical practice.
Keywords: senioři; medicína založená na důkazech; Drug Interactions; lékové interakce; lékové předpisy; Drug Prescriptions; Evidence-Based Medicine; nežádoucí účinky léčiv; Humans; Drug-Related Side Effects and Adverse Reactions; Aged; Drug Utilization Review; lidé; hodnocení spotřeby léčiv